Mining the forests: do protected areas hinder mining-driven forest loss in Sub-Saharan Africa? - (:unkn) unknown (My University, 2023)
African countries are natural resource-rich. The continent has natural forests, homes of endemic biodiversity and various ores. This richness brings hope for sustainable and inclusive development in a continent whose population is rapidly growing. It also raises fears of environmental degradation. This article studies mining-driven deforestation using unique finescale data from 2001 to 2019. The dataset covering all Sub-Saharan African countries entails 2,207 polygons with an average size of about 12,000 square kilometres. 926 polygons were forested in 2001, of which 198 hosted industrial mines. A spatial autoregressive model allows taking dependence between deforestation decisions at the polygon level. The econometric results show that an additional mine increases deforestation by about 155 square kilometres. Protected areas mitigate deforestation poorly. One hundred square kilometres under protected areas enable only a 9.7 square kilometres reduction in forest loss. More than doubling protected areas would be necessary to offset mining-driven forest loss. Protected areas cannot alone mitigate the adverse effects of mining on forest loss and other environmental consequences. Moreover, the effectiveness of protected areas is not uniform across space: it vanishes in highly conflicted regions.
Keywords: African Research